Metathesis of a UV imido complex: a route to a terminal UV sulfide. Issue 8 (5th June 2017) - Kelly, Rory P.; Falcone, Marta; Lamsfus, Carlos Alvarez; Scopelliti, Rosario; Maron, Laurent; Meyer, Karsten; Mazzanti, Marinella
Abstract : The metathesis reaction of a U V imido complex supported by sterically demanding tris( tert -butoxy)siloxide ligands with CS2 afforded a terminal U V thiocarbonate but metathesis with H2 S afforded the first example of a terminal U V sulfide. Abstract : Herein, we report the synthesis and characterisation of the first terminal uranium(v ) sulfide and a related U V trithiocarbonate complex supported by sterically demanding tris( tert -butoxy)siloxide ligands. The reaction of the potassium-bound U V imido complex, [U(NAd)OSi(O t Bu)3 4 K] (4 ), with CS2 led to the isolation of perthiodicarbonate [K(18c6)]2 [C2 S6 ] (6 ), with concomitant formation of the U IV complex, [UOSi(O t Bu)3 4 ], and S{C{NAd. In contrast, the reaction of the U V imido complex, [K(2.2.2-cryptand)][U(NAd)OSi(O t Bu)3 4 ] (5 ), with one or two equivalents of CS2 afforded the trithiocarbonate complex, [K(2.2.2-cryptand)][U(CS3 )OSi(O t Bu)3 4 ] (7 ), which was isolated in 57% yield, with concomitant elimination of the admantyl thiocyanate product, S{C{NAd. Complex7 is likely formed by fast nucleophilic addition of a U V terminal sulfide intermediate, resulting from the slow metathesis reaction of the imido complex with CS2, to a second CS2 molecule. The addition of a solution of H2 S in thf (1.3 eq.) to4 afforded the first isolable U V terminal sulfide complex, [K(2.2.2-cryptand)][USOSi(O t Bu)3 4 ] (8 ), in 41% yield. Based on DFT calculations, triple-bond character with a strong covalent interaction is suggested for the U–S bond in complex7 .